Answer:x = - 52
Explanation:
The given equation is expressed as
x/3-2/3=-18
The first step would be to find the lowest common multiple of denominators of the left hand side and the right hand side of the equation. The lowest common multiple is 3
Then we would multiply the left hand side and the right hand side of the equation by the lowest common multiple. It becomes
x/3 × 3 - 2/3 × 3 = -18 × 33
x - 2 = - 54
Adding 2 to the left hand side and the right hand side of the equation, it becomes
x - 2 + 2 = - 54 + 2
x = - 52